A Plausible God : Secular Reflections On Liberal Jewish Theology. (Fordham University Press, 2006)
A Plausible God evaluates the new God by analyzing the theology of three recent Jewish thinkers --Mordechai Kaplan, Michael Lerner, and Arthur Green--and compares faith in the new God to disbelief in any gods. Mitchell Silver reveals what is at stake in the choice between naturalistic liberal theology and a nontheistic naturalism without gods. Silver poses the question: "If it is to be either the new God or no God, what does--what should--determine the choice?" Although Jewish thinkers are used as the primary exemplars of new God theology, Silver explores developments in contemporary Christian thought, Eastern religious traditions, and "New Age" religion. A Plausible God constitutes a significant contribution to current discussions of the relationship between science and religion, as well as to discussions regarding the meaning of the idea of God itself in modern life.